ENERGY SYSTEM MODELS FOR SUB-SAHARAN AFRICAN COUNTRIES – A SYSTEMATIC REVIEW - DIOHA M.O. (Journal of Sustainable Energy, 2017)
The demand for energy in Sub-Saharan African (SSA) countries is rapidly increasing. This can be attributed to the increase in human population and standard of living in the region. Owing to the increasing energy demand, there is a need for proper energy planning. Energy system models are used in exploring the energy futures of countries and regions. Use of the wrong models has resulted in unrealistic projections and consequently poor energy policies. It is against this backdrop that this study was conceived. This paper aims to identify what class of energy system models that are most suitable for energy system analysis in SSA countries. Literature was initially reviewed to understand the basic characteristics of the energy systems of SSA countries. The paper then heads on to systematically identify what types of energy system models have been used in SSA countries, using the Scopus database search platform. The result of this extensive review suggests that the bottom-up optimization and the accounting framework class of energy models are best suited for SSA countries. However, the paper further opine that the existing energy system models are not capable of characterizing the energy system of SSA countries fully. Hence, there is a need to develop new energy system models or modify the already existing ones in order to capture all the features of SSA countries. Thus, this study will be of importance to energy analysts, researchers and policy makers when selecting energy system models.